Creativity of Physical Education Teachers in Learning Rhythmic and Floor Gymnastics at Senior High Schools in Kebumen Regency - Luthfi, Auliya; Rumini, Rumini; Priyono, Bambang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
This study aims to analyze the creativity of Physical Education (PE) teachers in teaching rhythmic gymnastics and floor gymnastics at Public Senior High School (PSHS) at Kebumen in 2021. Qualitative analytical research methodology, data collection techniques such as observation, interviewing, and documentation. Primary data include The certified PE teachers were as participant in this study, peers, and school principal, while secondary data sources include observations, interviews, and documents such as lesson plans, syllabus, annual program, semester program, and infrastructure. The study's findings indicate that: 1) In the Kebumen regency, the PE teacher used a variety of media, both audio and visual. 2) PE teacher of PSHS in Kebumen regency conducts curriculum development, chooses the right media, uses learning methods and conducts evaluations. 3) PE teachers attract attention with media, accuracy and continuous involvement of learning media. Conclusions: 1) PE teachers in Kebumen regency State Senior High Schools have a reasonably high level of imagination when it comes to learning rhythmic gymnastics; 2) PE teachers in Kebumen regency State Senior High Schools have a high level of creativity when it comes to learning floor gymnastics. 3) Students showed a strong understanding of rhythmic gymnastics and floor exercises. Suggestions: 1) To the PE teachers at Kebumen regency, continually strive to develop their creativity; 2) To the PE teachers at Kebumen regency, it is necessary to maintain a systematic and structured method. 3) Schools require additional facilities.